The intergenerational cycle of child maltreatment - Continuity versus discontinuity - DePanfilis, Diane (Journal of interpersonal violence, 1996)
Few studies have focused on identifying characteristics that discriminate between parents who break versus those who perpetuate intergenerational cycles of child maltreatment. Both the dose and the attachment hypotheses were examined in this study of 213 mothers maltreated as children in one of three ways (beatings, neglect, or sexual abuse). Maltreatment continuity versus discontinuity was assessed through substantiated reports to a Child Protective Services (CPS) agency over a 7-year period. Findings were consistent with the attachment hypothesis. Poorer quality attachment relationships in childhood increased the probability of transmission. Findings were consistent with the dose hypothesis for only one conceptualization of dose. Those mothers who had experienced severe forms of sexual abuse (experienced coitus vs. did not) were more likely to have a maltreated child. These findings are discussed in terms of current theory and research on intergenerational maltreatment